Accessory Soleus Muscle: Two Case Reports with a Completely Different Presentation Caused by the Same Entity - Mihovil Plečko; Igor Knežević; Damjan Dimnjaković; Mario Josipović; Ivan Bojanić (Case Reports in Orthopedics)
Accessory soleus muscle (ASM) is a rare supernumerary anatomical variant that commonly presents as a posteromedial ankle swelling, which may become painful during physical activity. As it may mimic a soft tissue tumor, it is essential to differentiate this condition from ganglion, lipoma, hemangioma, synovioma, and sarcoma. However, ASM may also present with a painful syndrome, characterized by pain and paresthesia of the ankle and foot, mimicking the tarsal tunnel syndrome (TTS). Two cases of ASM are presented in this article. The first case had a typical presentation with painful posteromedial ankle swelling. After the initial assessment, the diagnosis was confirmed by magnetic resonance imaging (MRI), and ASM was treated by complete resection. The second case presented with pain and paresthesia in the right ankle and foot, but no swelling was noticeable. It was initially misdiagnosed by a rheumatologist and afterward overlooked on an MRI by a musculoskeletal radiology specialist and therefore mistreated by numerous physicians before being referred to our outpatient clinic. After further assessment, the diagnosis has been confirmed, and ASM was treated by complete resection combined with tarsal tunnel decompression. To the best of our knowledge, this is the first case reported in which ASM caused symptoms but presented without posteromedial swelling. This might be due to a proximally positioned belly of the ASM, followed by a tendinous insertion on the medial side of the calcaneus.